Modelling Command and Control: Event Analysis of Systemic Teamwork - Stanton, Neville A.; Baber, Chris; Harris, Don (CRC Press, 2008)
Command and control environments continue to represent a challenging domain for human factors research. Modelling Command and Control takes a broad view of command and control research, to include C2 (command and control), C3 (command, control and communication), and C4 (command, control, communication and computers) as well as human supervisory control paradigms. The book presents case studies in diverse military applications (e.g. land, sea and air) of command and control. While the domains of application are very different, many of the challenges they face share interesting similarities.